Edukasi 6 Langkah Cuci Tangan Sebagai Upaya Pencegahan Covid-19 - Intan Diah Pramithasari, Ns., M.Kep. (JPS : Jurnal Pengabdian Serulingmas, 2021)
The development of the Novel Coronavirus disease in several countries has caused a high level of panic for the public. The development of this information, of course, increases the public's concern about the possibility of spreading the disease that is increasingly widespread in the territory of Indonesia. This condition of concern is used by a group of irresponsible people to spread the news of corona events that cannot be accounted for. This has further fueled public fear of the spread of the Corona disease. Therefore, it is necessary to increase the understanding and knowledge of the community about the disease as well as simple prevention efforts that can be done. This effort can be made to influential community groups in the surrounding environment or community leaders. The purpose of this activity is to increase the knowledge and skills of the community in preventing Covid-19 through clean and healthy living behaviors, one of which is the habit of washing hands with soap. The method used is through lectures, simulations, and demonstrations on 58 participants. The results of the service showed that there was an increase in knowledge of the target of counseling about the Novel Coronavirus (2019-nCoV), signs and symptoms, and prevention efforts. The target group can practice the 6 steps of handwashing according to WHO properly and sequentially.